The wing mites (Acari: Spinturnicidae) of the Turkish bats, including new records: DOI: 10.48129/kjs.11569 - Karataş, Ahmet; Ferhat Toprak (Kuwait Journal of Science, 2022)
This study is based on 93 Spinturnicidae specimens collected on 312 bat specimens obtained from various parts of Turkey. As a result of the study, Eyndhovenia euryalis (Canestrini, 1884), Spinturnix acuminatus (C. L. Koch, 1836), S. myoti (Kolenati, 1847), S. psi (Kolenati, 1856), S. plecotinus (C. L. Koch, 1839), and S. punctata (Sundevall, 1833) species were identified. Of these species, S. plecotinus, and S. punctata are new records for the Turkish fauna.